ELEGANT EXTORTION "The Ambiguity of Restaurant Service Charges Through the Perspective of Consumer Protection Law" - Dimas Aryo Yuwono; Karya Bima Satria Y (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research examines the ambiguity surrounding the imposition of service charges in restaurants, particularly from the perspective of consumer protection law in Indonesia. It argues that the current practice, where service charges are often mandatory and lack transparency, can be viewed as a form of "elegant extortion." The study analyzes the legal framework, including the Consumer Protection Law and relevant regulations, to assess the rights of consumers and the obligations of restaurant owners. It explores the concepts of justice, balance, and fairness in consumer-business relationships, drawing on philosophical perspectives to propose a legal construction that ensures transparency, freedom of choice, and equitable practices regarding service charges in restaurants outside of hotels. The paper concludes by offering recommendations for both government regulation and restaurant management practices to better protect consumer rights and promote fair business practices.